Pengaruh Penggunaan Gadget terhadap Perilaku dan Prestasi Siswa Sekolah Dasar SD Muhammadiyah 1 - Nursyaida; Yulanti S. Mooduto; Rahmat (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to determine the effect of gadget use on the social and academic behavior of elementary school students. The study used a quantitative approach with a survey method of 120 students from several elementary schools in urban areas. The instruments used were questionnaires and student academic achievement data analyzed using simple linear regression. The results showed that there was a significant relationship between the intensity of gadget use and a decrease in positive social behavior, such as social skills and empathy. In addition, a negative correlation was found between the duration of gadget use and academic achievement, where students who used gadgets for more than three hours per day tended to have lower academic grades. The conclusion of this study is that excessive gadget use can have a negative impact on the social behavior and academic achievement of elementary school students. Therefore, supervision and regulation of gadget use time by parents and teachers are needed to minimize negative impacts and direct the use of technology positively in the learning process.